Memory of the Sacred Place: A Reading of “A Return to Qudos” by Hania Lalla Razika - AHKOU, SAMIA (Milev Journal of Research and Studies, 2015)
The return to the place « Qudos », establishes the Arab identity and the spirit of belonging to the Palestinian cause which ignited poetic imagination and made resistance a clever act. It summarized the intellectual dimension which moves the confession ground. And it decorates the poem by containing historic data and the eradication of the Zionist state from the body of the nation and its symbolic death, though only on paper as an alternative which realizes psychological and spiritual balance. It also enlarges the circle of touch between the self and its Arab identity. Hence, the issue of coming back has come as is a central one in poetry, because it treats the Palestinian cause summarized in the Qudos issue.